Strategic Communication in Digital Activism: A Narrative Review Across Global South Movements - Lisnawati (Communica : Journal of Communication, 2024)
Digital activism has emerged as a powerful mechanism for social change, leveraging communication strategies on social platforms to drive engagement, mobilization, and advocacy. This structured narrative review synthesizes and analyzes key strategies used in digital activism across diverse contexts, with a particular focus on underexplored regions in the Global South. A total of 72 peer-reviewed articles published between 2010 and 2024 were systematically identified from Scopus, Web of Science, Google Scholar, and PubMed. A thematic synthesis method was applied to examine patterns across communication strategies, platform affordances, and systemic challenges. Findings highlight the effectiveness of hashtags, videos, and infographics in enhancing audience reach and solidarity, particularly when amplified by influencers and algorithmic visibility. Twitter, Facebook, and Instagram show complementary roles in mobilization, while activists in marginalized communities face persistent obstacles such as surveillance, censorship, and economic inequality. The review concludes that policy interventions are essential to safeguard inclusive digital activism, and recommends further localized studies to explore context-specific communication strategies and resilience frameworks.